Buddhism-related Tuvan personal names - Suvandii, Nadezhda D. (The New Research of Tuva, 2021)
The article aims to systematize contemporary Tuvan anthroponyms which are linked to Buddhism and were originally borrowed from Tibetan and Sanskrit via Mongolian language. The material presented here was collected by the author in the course of her comprehensive expeditions to Khovd, Bayan-Ölgii, and Khövsgöl aimags of Mongolia and some rayons of the Republic of Tuva. As a result of our study, eight type of personal names have been identified: 1) anthroponyms stemming from the titles of the holy books and fragments of the sutras read during prayers in Buddhist monasteries; 2) personal names linked to the names of Buddhist deities; 3) those stemming from the names of the planets; 4) those repre-senting the personality and state of those they denote; 5) personal names stemming from words for accessories used by the clergy; 6) names linked to words for vegeta-tion; 7) anthroponyms formed from the roots meaning jewels, metals, etc.; and 8) personal names reflecting virtues of Buddhist worship. For each type, examples are provided in the article. Also traced are the phonetical transformations which are manifest in almost any borrowed word.
Keywords: Tuvan language; onomastics; name list; personal name; Buddhism; lexical-semantic group; anthroponym; borrowed name; Tuvans; Tuva; Mongolia; Mongolian Tuvans